Regional connotations in the school environments in Deçan - Dacaj Brahimaj, Rajmonda (Technium Social Sciences Journal, 2023)
This research belongs to the field of sociolinguistic, trying to bring linguistic changes in relation to society and emphasising the power of sociolinguistic factors in the appearance of these changes. The object of this study are the lectures of some teachers with special word stress, and some regional connotations which came out during this process. The gathering of material to conduct this research was made in the school environments in Deçan, during teaching hours while maintaining the adherence of the research, therefore this has brought out the real state of Albanian language in those environments. The work has been done drawing out only dialectal forms which we have noticed during the lecture of subjects, which we have analyzed in the phonetic aspect and in morphological aspect, comparing them with standardized forms. Phonetic analysis involve word review in the vowel and consonant system, vowel groups and consonant groups, and some more highlighted phonetic occurences. The results have proved that the traditional speech does not disappear without leaving its trace despite the rise in the standard language level. The purpose of this research is to identify and analyze the regional connotations in the lectures ofthe teachers in the school environments in Deçan. Within this paperwork we will see some dialectal forms which remained in use. The identification and gathering of the material was done by participating as an observer in teaching hours of the teachers, always, not telling them the true purpose of our presence, so that we could get the material in the most natural way. While gathering the material we have used technical tools to record teachers voice. The collected material is used to highlight the regional connotations, on the other hand for their theoretical explanation we used the literature in the field of sociolinguistic.